2019
DOI: 10.1186/s12911-019-0751-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing factors militating against the acceptance and successful implementation of a cloud based health center from the healthcare professionals’ perspective: a survey of hospitals in Benue state, northcentral Nigeria

Abstract: Background Cloud based health platforms (CBHP) have tremendous capacity to meet patient’s health needs. The benefits inherent in CBHP position it to be relevant for efficient healthcare delivery. Nonetheless, studies have shown that the adoption of new technologies is sometimes a challenge especially in developing nations. This study, therefore, aim to examine, identify and evaluate the factors affecting healthcare professionals’ intention to accept the cloud-based health center (CBHC) in developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 58 publications
8
26
0
Order By: Relevance
“…In this study, facilitating condition played an important role in predicting health care providers intention to use EMRs (β = 0.23, p < 0.001). This is in line with a study conducted in North Central Nigeria (β = 0.11, p < 0.05) [44],South Africa (β = 0.28, p < 0.05) [45],Malaysia (β = 0.16,p < 0.05) [46] and Ontario Canada (β = .11, p < .01) [32]. It could be due to the fact that health care providers believe that the resources and technical support should be available to use the EMR in their workplace [43].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, facilitating condition played an important role in predicting health care providers intention to use EMRs (β = 0.23, p < 0.001). This is in line with a study conducted in North Central Nigeria (β = 0.11, p < 0.05) [44],South Africa (β = 0.28, p < 0.05) [45],Malaysia (β = 0.16,p < 0.05) [46] and Ontario Canada (β = .11, p < .01) [32]. It could be due to the fact that health care providers believe that the resources and technical support should be available to use the EMR in their workplace [43].…”
Section: Discussionsupporting
confidence: 92%
“…39 Our findings were consistent with those of prior studies concerning the technological adoptions in health care. 22,39 A study conducted to identify predictors of the intention of healthcare professionals to use a new cloud base health platform (CBHP) technology found FC as a significant factor related to intention to accept and use CBHP. 39 Asua et al 22 identified FC to be the most powerful predictor of medical professionals' intention to use a telemonitoring system.…”
Section: Discussionsupporting
confidence: 92%
“…22,39 A study conducted to identify predictors of the intention of healthcare professionals to use a new cloud base health platform (CBHP) technology found FC as a significant factor related to intention to accept and use CBHP. 39 Asua et al 22 identified FC to be the most powerful predictor of medical professionals' intention to use a telemonitoring system. Therefore, it was concluded that participants are more likely to consider telehealth to be a helpful system if they believe that it has a vigorous infrastructure to support the use of telehealth.…”
Section: Discussionmentioning
confidence: 99%
“…When the external users try to enter the Cloud computing network, so, first they undergo through the vital barrier of firewall that provides networks security and allow only those users who are compliant and give safety from different attacks such as HTTP DoS (Denial of service) or brute force attack. [30,31].…”
Section: Related Workmentioning
confidence: 99%